Compliance applying OHS: Are knowledge and self regulation influence? - Kurniati, Hafidha Tri; Fathiyah, Kartika Nur (Psychology, Evaluation, and Technology in Educational Research, 2021)
Occupational Health and Safety (OHS) is a work activity to prevent work accidents. Work accidents caused by workers are motivated by workers' non-compliance at work. Compliance is known as a person's measure to act so that undesirable things do not happen, such as work accidents. OHS knowledge and self-regulation affect a person's compliance to comply with OHS. The purpose of this study was to determine the influence of OHS knowledge and self-regulation on compliance applying OHS. The sample research involved as many as 80 chemistry students at Yogyakarta State University. The research data collection tools are the compliance questionnaire to apply OHS, self-regulation, and OHS knowledge. The data analysis technique used is the multiple linear regression test. The results showed that there was an effect of OHS knowledge and self-regulation on compliance applying OHS (p=0,000) with an effective contribution of 68.1%. It means that OHS knowledge and self-regulation can be a predictor for compliance applying OHS of students practising in chemical laboratories.